Flexible Road Pavement Thickness Planning using the 2017 Manual Road Pavement Design (MDPJ) Method and 1987 Component Analysis on the Jepara - Keling Road Section - Umam, Khotibul (Universitas Negeri Padang, 2023)
The increase in the volume of vehicles on the Jepara - Keling road has resulted in a decrease in the quality of road services, moreover, it has been exacerbated by the passing vehicles which often exceed their carrying capacity, thus accelerating road damage. Therefore, road planning efforts are needed to maintain road function from various potential damages that occur. The purpose of this thesis is to plan a flexible pavement thickness that is able to serve the volume of vehicles and withstand the loads of passing vehicles. Meanwhile, before planning a road, it is necessary to know the condition of the road, field CBR data, average daily traffic data and also need to plan what material the road will be built with. The approach method used in planning the thickness of the flexible pavement is using the 2017 Road Pavement Design Manual (MDPJ) method and the 1987 Component Analysis method. Based on the calculations that have been carried out, it is obtained that the thickness of the flexible pavement structure design is obtained for each layer using the Road Pavement Design Manual (MDPJ) method. ) 2017 are as follows: for 4 cm thick AC-WC layer, 6 cm thick AC-BC layer, 16 cm thick AC-Base layer, and 30 cm thick Class A LPA layer. Whereas using the 1987 Component Analysis method, the thickness for each layer was obtained as Asphalt Concrete MS 740: 10 cm, Class A Crushed Stone LPB: 25 cm, Class A Sand and Stone LPB: 22 cm